Magmatic and tectonic patterns over the Northern Victoria Land sector of the Transantarctic Mountains from new aeromagnetic imaging - Ferraccioli, F.; Armadillo, E.; Zunino, A.; Bozzo, E.; ROCCHI, SERGIO; ARMIENTI, PIETRO (Tectonophysics, 2009)
New aeromagnetic data image the extent and spatial distribution of Cenozoic magmatism and older basement features over the Admiralty Block of the Transantarctic Mountains. Digital enhancement techniques image magmatic and tectonic features spanning in age from the Cambrian to the Neogene. Magnetic lineaments trace major fault zones, including NNW to NNE trending transtensional fault systems that appear to control the emplacement of Neogene age McMurdo volcanics. These faults represent splays from a major NW–SE oriented Cenozoic strike-slip fault belt, which reactivated the inherited early Paleozoic structural architecture. NE–SW oriented magnetic lineaments are also typical of the Admiralty Block and reflect post-Miocene age extensional faults. To re-investigate controversial relationships between strike-slip faulting, rifting, and Cenozoic magmatism, we combined the new aeromagnetic data with previous datasets over the Transantarctic Mountains and Ross Sea Rift. Two key observations can be made from our aeromagnetic compilation: 1) Cenozoic alkaline intrusions along the margin of the Ross Sea Rift lie oblique to the NW–SE strike-slip faults and are not significantly displaced by them; 2) the Southern Cross and the Admiralty Blocks are much more significantly affected by Cenozoic magmatism compared to the adjacent tectonic blocks, thereby indicating major tectono-magmatic segmentation of the Transantarctic Mountains rift flank. We put forward three alternative tectonic models to explain the puzzling observation that major Cenozoic alkaline intrusions emplaced along the Ross Sea Rift margin show no evidence for major strike-slip displacement. Our first model predicts that the alkaline intrusions were emplaced along left-lateral cross faults, which accommodated distributed right-lateral shearing. In contrast, our second model does not require major distributed strike-slip shearing, and relates the emplacement of Cenozoic alkaline intrusions to sea-floor spreading in the Adare Basin, coupled with intracontinental ...